Energetic Interactions Between Minas Gerais State and the Rest of Brazil: An Inter-Regional Input-Output Analysis - Fernando Perobelli; Rogerio Silva De Mattos; Weslem Rodrigues (European Regional Science Association (ERSA), 2006)
This paper analyses the interdepence between the State of Minas Gerais and the rest of Brazil with regard to energy consumption. A hibryd interregional input-output model, by means of which energy intensity measures are computed, is used to undertake the analysis. The energy measures allow, for instance, to assess the degree in which a sector production in Minas Gerais impacts the energy consumption inside and outside the state. Also, the measures allow to assess the degree in which sector production in the rest of Brazil (outside Minas Gerais) impacts energy consumption inside and outside the state. The analysis presents disaggregate information for 14 economic sectors, two spatial areas (Minas Gerais and the rest of Brazil), and one kind of energy use (total energy), thus allowing to trace an accurate portrait of interdependence patterns.
Keywords: 330